Flute Art in the Light of the Historical Significance of Methodological Schools and Directions in Music Education: The Past and Present - Karpyak, Andriy (Journal of History Culture and Art Research, 2020)
Professional activity of the flutist encompasses a sizeable repertoire, in terms of its volume and time span, comprising works for the flute solo, as well as with ensemble and orchestra. It presupposes the available deep artistic knowledge, orientation in the subjects of teaching this profession, history and theory of music, harmony, acoustics, psychology, etc. By defining basic priorities in the formation of the performing mastery of the flutist, this article focuses on the progressive provisions of psychophysiological methods. It monitors the historical path and the evolution of this branch via the examination of major publications, professional theses that defined the facets of the entire eras of this direction of instrumental art. Nowadays the results of psychophysiological research in the field of music pedagogy give us a great opportunity to improve practising methods and realize the misunderstandings in the interpretation of concepts, differentiating their meaning and role in the work of a musician. They also combine the properties of content (reason) and expressiveness (consequence) of performing art into a single complex of creative artistic flutist activity. Under anatomical and physiological circumstances the musician’s performing technique, such as fixation of body posture elements and the passivity of hearing, achieving free, natural movements, mainly stereotypical reaction-response to image-stimulus and struggle with variability of technical means acquires an active research character. A contradictory condition for the emergence of reflexes in psychotechnics and search for sound freedom, which previously played an ascertaining role, call for reconsideration under these new conditions. The focus is shifted towards the development of artistic thinking of professional musicians, the acquisition of knowledge and the ability to relate vivid associative impressions with intonational phenomena and processes, as well as the formation of the performing apparatus and mastering the art of interpretation.